ANAEROBIC DIGESTION OF SEWAGE SLUDGE USING SEQUENTIAL REACTORS: START- UP AND SYSTEMS STABILIZATION - PAULA JR, DURVAL R. DE; ROSTON, DENIS M.; NOUR, EDSON ABDUL.A.; MORAES, LUCIANA M.; CAMARGO, SANDRA APARECIDA R. DE (Revista Brasileira de Engenharia de Biossistemas, 2008)
The objective of this work was the implantation and evaluation of three sludge anaerobic digestion systems. The system A configuration was defined by five continuous flow sequential anaerobic reactors (SAR) with effluent recycling. System B had the same layout, but recirculation was substituted by mechanical mixers installed in each reactor. System C was composed by only one continuous flow stirred tank reactor. The systems were evaluated by weekly monitoring of physicalchemical parameters. Samples were taken from influent, effluent and intermediary ports during an operation period of 115 days. During the most stable operational period (PHASE II), the results indicated total solids removal rate of 95, 40 and 29%, and volatile solids removal rate of 95, 34 and 22%, for System A, B and C, respectively. The sequential anaerobic reactors (System A and B) presented better performance than conventional digestor (System C).